Office and ambulatory pulse pressure - association with clinical characteristics and cardiovascular risk factors in normoalbuminuric patients with type 2 diabetes (ROADMAP study) - Januszewicz, Andrzej; Ritz, Eberhard; Viberti, G.; Mimran, A.; Rabelink, A. J.; Rump, L. C.; Ruilope, L. M.; Katayama, S.; Ito, S.; Izzo, J. L.; Haller, H. (Journal of human hypertension, 2011)
To investigate the association of office and ambulatory 24-h pulse pressure (PP) with clinical characteristics and cardiovascular risk factors in normoalbuminuric type 2 diabetic patients enrolled to the Randomised Olmesartan and Diabetes Microalbuminuria Prevention study, 4449 patients (2054 male and 2395 female; mean age 57.7±8.7 years) with type 2 diabetes, normoalbuminuria and at least one additional cardiovascular risk factor were included into the analysis. After adjustment by age, there were significant correlations between office PP and presence of hypertension (r=0.24; P<0.001), presence of cardiac and vascular disorders (r=0.17; P<0.001), metabolic syndrome (r=0.10; P<0.001), duration of diabetes (r=0.09; P<0.001), fasting blood glucose (r=0.08; P<0.001), albumin/creatinine ratio (r=0.07; P<0.001), insulin treatment, glycosylated haemoglobin (HbA1c), male gender and current smoking. In the subgroup of 1234 patients with ambulatory blood pressure measurement performed, ambulatory PP adjusted for office PP correlated with fasting blood glucose (r=0.16; P<0.001), metabolic syndrome (r=0.14; P<0.001), albumin/creatinine ratio (r=0.11; P<0.001) and indices of glycemic control (HbA1c: r=0.11; P<0.001). In this group of normoalbuminuric type 2 diabetic patients, office and ambulatory PP were associated with duration of diabetes, indices of glycemic control and cardiovascular risk factors. There was relationship between office and ambulatory PP and albuminuria even within normal albuminuria range.
published online 9 December 2010
Gesehen am 04.07.2022